P3.009 Prevalence of Chlamydia Trachomatis and Neisseria Gonorrhoea Infection in Pregnant Women Enrolled in a Large Multicenter Clinical Trial. (13th July 2013) - Osiecki, J; Duncan, J; Lewinski, M; Liesenfeld, O
Abstract : Background: Pregnant women infected with sexually transmitted diseases are at higher risk for miscarriage, pre-term delivery, low birth weight, and morbidity in the neonate associated with transmission of pathogenic agents. Treatment guidelines recommend screening pregnant women for Chlamydia trachomatis (CT) and Neisseria gonorrhoea (NG) on the first prenatal visit. This study was performed to determine the frequency of CT and NG infection observed in pregnant women enrolled in a large clinical trial study population. Methods: This multicenter retrospective cohort analysis was performed with data collected during the VENUS clinical trial, a study characterising the clinical performance of the cobas ® CT/NG Test on the cobas ® 4800 system. Two FDA-cleared nucleic acid amplification tests (NAATs) were used as comparator assays. Obstetrics-gynaecology practises, family planning clinics, and STD clinics from diverse settings in the United States served as specimen collection sites. Patient infection status (PIS) was defined as positive when results from NAATs with different target regions generated positive results with collected samples. Results: Of 5, 269 enrolled participants, 281 of 4315 eligible women (6.5%) were found to be positive for CT infection and 69 of 4314 (1.6%) were positive for NG according to PIS outcomes. Alternatively, 16 of 178 eligible pregnant women (9.0%) were positive for CT, where 2 of 178 pregnant women (1.1%) were considered positive for NG by PIS. Conclusion: Screening of pregnant women for CT and NG with the cobas ® CT/NG Test and two additional NAATs during the VENUS clinical trial revealed the prevalence of CT and NG infections are comparable to rates observed in the general female population.